Size of an interspecific competitor may be a source of information in reproductive decisions. (13th December 2022) - Hämäläinen, Reetta; Välimäki, Panu; Forsman, Jukka T
Abstract: Animals use inter-specific cues as a source of information in decisions-making, but the full costs and benefits of inter-specific information use are unknown. We tested whether pied flycatchers use the body size and clutch size of great tits as cues in their reproductive decisions and what are the possible fitness consequences as a function of great tit size. The size of great tit females associated positively with flycatcher's probability to settle near a tit nest over a territory further away. Flycatcher egg mass was positively correlated with great tit female size regardless of flycatcher territory choice. However, in flycatchers that had chosen to nest near great tits, the size of nestlings decreased in relation to increasing great tit female size. Our results demonstrate the use of size of inter-specifics as a cue in reproductive decisions and the trade-off between the value of information and costs of competition information users face when using inter-specific information in decision-making.